2017
DOI: 10.3389/fphys.2017.00980
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression Network Approach Reveals Functional Similarities among Diseases Affecting Human Skeletal Muscle

Abstract: Diseases affecting skeletal muscle exhibit considerable heterogeneity in intensity, etiology, phenotypic manifestation and gene expression. Systems biology approaches using network theory, allows for a holistic understanding of functional similarities amongst diseases. Here we propose a co-expression based, network theoretic approach to extract functional similarities from 20 heterogeneous diseases comprising of dystrophinopathies, inflammatory myopathies, neuromuscular, and muscle metabolic diseases. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Colors on the tree indicate the clusters/grouping of diseases, while the red line indicates the threshold used for clustering. (Reprinted with permission from Mukund and Subramaniam (). Copyright 2017 Frontiers Publication)…”
Section: Common Molecular Mechanisms Underlying Muscle Diseasesmentioning
confidence: 99%
“…Colors on the tree indicate the clusters/grouping of diseases, while the red line indicates the threshold used for clustering. (Reprinted with permission from Mukund and Subramaniam (). Copyright 2017 Frontiers Publication)…”
Section: Common Molecular Mechanisms Underlying Muscle Diseasesmentioning
confidence: 99%
“…Applications of gene coexpression network analysis have been successfully applied in ALS. Multiple gene coexpression studies have revealed several pathways believed to be implicated in ALS, including cell adhesion, calcium ion binding, inflammatory processes, and tumour necrosis factor (TNF) signalling [72,73,74,75,76,77]. Brohawn et al took gene expression data gathered from seven ALS spinal cord samples and eight control spinal cord samples [78].…”
Section: Omics Data In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Systems biology has also been employed in the identification of novel biomarkers, characterization of patients, and stratification of heterogenous cancer patients ( Benfeitas et al, 2019 ; Bidkhori et al, 2018 ; Lee et al, 2016 ). Specifically, integrated networks (INs) ( Lee et al, 2016 ) and co-expression networks (CNs) ( Lee et al, 2017 ) have been proven to be robust methods for revealing the key driver of metabolic abnormalities, discovering new therapy strategies, as well as gaining systematic understanding of diseases ( Bakhtiarizadeh et al, 2018 ; Mukund and Subramaniam, 2017 ).…”
Section: Introductionmentioning
confidence: 99%